2011
DOI: 10.1128/jvi.00410-11
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma Virus Lacking the Pyrin-Like Protein M013 Is Sensed in Human Myeloid Cells by both NLRP3 and Multiple Toll-Like Receptors, Which Independently Activate the Inflammasome and NF-κB Innate Response Pathways

Abstract: The myxoma virus (MYXV)-encoded pyrin domain-containing protein M013 coregulates inflammatory responses mediated by both the inflammasome and the NF-κB pathways. Infection of human THP-1 monocytic cells with a MYXV construct deleted for the M013 gene (vMyxM013-KO), but not the parental MYXV, activates both the inflammasome and NF-κB pathways and induces a spectrum of proinflammatory cytokines and chemokines, like interleukin-1β (IL-1β), tumor necrosis factor (TNF), IL-6, and monocyte chemoattractant protein 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 56 publications
(77 reference statements)
0
46
0
Order By: Relevance
“…Several studies have recently revealed the in vivo role of ASC in different physiological and pathological events associated with inflammation (20). DNA viruses, including vaccinia virus, adenovirus, myxoma virus, and mouse cytomegalovirus (21)(22)(23), and RNA viruses, such as influenza A virus, Sendai virus, human respiratory syncytial virus, and encephalomyocarditis virus (EMCV), utilize the inflammasome assembly to induce IL-1␤ production (12,24,25). In another seminal study, Ichinohe et al reported that ASC inflammasomes play a central role in innate and adaptive immunity to influenza virus (26).…”
mentioning
confidence: 99%
“…Several studies have recently revealed the in vivo role of ASC in different physiological and pathological events associated with inflammation (20). DNA viruses, including vaccinia virus, adenovirus, myxoma virus, and mouse cytomegalovirus (21)(22)(23), and RNA viruses, such as influenza A virus, Sendai virus, human respiratory syncytial virus, and encephalomyocarditis virus (EMCV), utilize the inflammasome assembly to induce IL-1␤ production (12,24,25). In another seminal study, Ichinohe et al reported that ASC inflammasomes play a central role in innate and adaptive immunity to influenza virus (26).…”
mentioning
confidence: 99%
“…It has been demonstrated that viral infections can induce the NLRP3 inflammasome activation (10,17,(58)(59)(60). We then investigated whether the NLRP3-ASC-caspase-1 complex is formed in response to HP-PRRSV infection.…”
Section: Hp-prrsv Infection Induces Nlrp3-dependent Inflammasome Actimentioning
confidence: 99%
“…Several types of viruses, including influenza A virus, dengue virus, hepatitis C virus, adenovirus, varicella zoster virus, encephalomyocarditis virus, vesicular stomatitis virus, myxoma virus, and respiratory syncytial virus have been found to induce IL-1␤ through the NLRP3 inflammasome (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Interestingly, HIV-1 infection has been reported to induce NLRP3 mRNA expression in monocyte-derived dendritic cells (32), and an SNP at the 3Ј UTR of the NLRP3 gene is associated with susceptibility to HIV-1 infection (33).…”
mentioning
confidence: 99%